A COMPLETE SOLUTION TO THE SPECTRUM PROBLEM FOR GRAPHS WITH SIX VERTICES AND UP TO NINE EDGES - Kolotoglu, Emre (UNIV CALGARY, DEPT MATH & STATISTICS, 2020)
Let G be a graph. A G-design of order n is a decomposition of the complete graph K-n into disjoint copies of G. The existence problem of graph designs has been completely solved for all graphs with up to five vertices, and all graphs with six vertices and up to seven edges; and almost completely solved for all graphs with six vertices and eight edges leaving two cases of order 32 unsettled. Up to isomorphism there are 20 graphs with six vertices and nine edges (and no isolated vertex). The spectrum problem has been solved completely for 11 of these graphs, and partially for 2 of these graphs. In this article, the two missing graph designs for the six-vertex eight-edge graphs are constructed, and a complete solution to the spectrum problem for the six-vertex nine-edge graphs is given; completing the spectrum problem for all graphs with six vertices and up to nine edges.
Keywords: graph design; DESIGN; EXISTENCE; Mathematics